Beyond the Rationality of Taste: Unpacking the Meaning of Identity in Papua People’s Culinary Design - Mambraku, Victor M. I. (Green Publisher Indonesia, 2025)
This study adopts a food design approach to investigate the impact of local identity on traditional cuisine belonging to the community of the Sentani people. The background highlights the importance of understanding and maintaining a unique cultural and culinary heritage when developing dining experiences that respect cultural roots. The ultimate goal was to integrate local identity into the food design. The two key questions were: (1) How can local identity be reflected in food components, such as raw materials, cooking techniques, and presentations? (2) How can food design that considers local identity enhance the dining experience? The research method involved the analysis of secondary data covering the culture, traditions, and history of Sentani, as well as an exploration of food design that incorporates elements of local identity. The main find-ings highlight the importance of using local raw materials and traditional cooking techniques and of emphasizing the aesthetics and stories behind Sentani dishes. The implication of this research is the development of a food menu that preserves the in-tegrity of Sentani culture while enabling innovations that respect local cultural roots. The results of this study illustrate that a food design approach that incorporates local identity can enrich the dining experience and support the sustainability of the local culinary culture. In conclusion, appreciation of local identity in Sentani food encourages innovative development that nurtures its cultural and culinary values.